Strategi Guru PAUD dalam Pembelajaran Seni Rupa 3D terhadap Fokus Anak ASD di TK Talenta Semarang - Intan Fadilah; Akaat Hasjiandito (Khirani: Jurnal Pendidikan Anak Usia Dini, 2026)
This study was conducted based on the importance of appropriate learning strategies to support the focus of children with Autism Spectrum Disorder (ASD) in early childhood education settings. Three-dimensional (3D) art learning was chosen because it provides direct visual, sensory, and motor experiences for children during the learning process. The study aimed to describe the strategies used by early childhood teachers in 3D art learning to support the focus of children with ASD and to identify factors influencing the success of the learning process. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving two classroom teachers and two children with ASD at TK Talenta, Semarang. The findings revealed that teachers applied several strategies, including the use of visual and concrete media, simple and gradual instructions, direct demonstrations, individual assistance, positive reinforcement, classroom environment management, and flexibility in adjusting activities to children’s interests. The success of the learning process was also influenced by individual characteristics of the children, interest in activities, classroom conditions, teacher involvement, and support from both the school and parents. The study indicates that 3D art learning can help support the focus of children with ASD when accompanied by appropriate teaching strategies and a conducive learning environment.